Roles of the Early Genes of Bacteriophage T7 in Shutoff of Host Macromolecular Synthesis - McAllister, William T. (1977)
Through the use of phage mutants in which various combinations of the early genes are active, and in which late gene expression is blocked, we have examined the roles of each of the five early gene products of bacteriophage T7 in regulating the synthesis of host RNA and proteins. At least two independent transcriptional controls operate during bacteriophage T7 development. The product of gene 0.7, acting alone, leads to a rapid (by 5 min) shutoff of host transcription. In the absence of gene 0.7 function, and in the absence of the phage-specified RNA polymerase, a delayed shutoff of host-dependent transcription begins at approximately 15 min after infection. This secondary control element requires either a functional gene 0.3 or gene 1.1. In the absence of any early gene products, host shutoff is not observed until much later in infection (>30 min). The delayed manner in which the products of genes 0.3 and 1.1 exert their effect suggests that their mode of action is indirect. Under conditions in which the late genes are transcribed (inefficiently) by the host RNA polymerase, gene 1.1 is observed to stimulate the synthesis of lysozyme (the product of a late phage gene). In contrast, when the late genes are transcribed by the phage-specified RNA polymerase (the product of gene 1), the kinetics of synthesis of the phage RNA polymerase itself, and of lysozyme, are not affected by the deletion of genes 0.3, 0.7, 1.1, and 1.3. We conclude that under these conditions, the products of these genes are required neither for regulation of expression of the late genes nor for the shutoff of early phage gene expression.